Analisis kemampuan komunikasi matematis siswa materi segiempat ditinjau dari self directing learning - Agnes Pujianti; Wahyu Setiawan; Heris Hendriana (IKIP Siliwangi, 2023)
The research was carried out with the aim of analyzing the mathematical communication skills of students on quadrilateral material in terms of self-directing learning. The method used is descriptive qualitative method. As many as 30 students of class VII A from SMP Pasundan 1 Cimahi were the subjects of this study. The data collection technique was in the form of a self-rating scale of self-directed learning (SRSSDL) questionnaire and a test instrument of 3 questions with indicators of written mathematical communication skills and interviews. The results showed that students with high self-directing learning had high mathematical communication skills by fulfilling all aspects of mathematical communication abilities. Students who are self-directing learning have average mathematical communication skills and are able to fulfill 2 aspects of mathematical communication skills, namely writing text and mathematical expression. Students whose self-directing learning is low have low mathematical communication skills which are only able to fulfill 1 aspect of mathematical communication ability, namely writing text and 1 indicator on the aspect of mathematical expression.